Wickie Wackie Music Festival 2017.
Wickie Wackie Music Festival 2017 held December 9, 2017 at Wickie Wackie Beach Bull Bay featuring the Grammy nominated Raging Fyah Jah9 and The Dub Treatment, Notis Heavyweight Rockaz, Earthkry-Chevaughn, Koffee-6 Points. Sound System (Rockaz Sound Station) Yaadcore and Gabrie Selassie.
Poster is located in drawer #1.
Keywords: Arts -- Music -- Jamaica; Posters -- Jamaica